Magnetism and Synchrotron Radiation: Towards the Fourth Generation Light Sources Proceedings of the 6th International School “Synchrotron Radiation and Magnetism”, Mittelwihr (France), 2012 - Beaurepaire, Eric.; Bulou, Hervé; Joly, Loic.; Scheurer, Fabrice; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Advances in the synthesis of new materials with often complex, nano-scaled structures require increasingly sophisticated experimental techniques that can probe the electronic states, the atomic magnetic moments and the magnetic microstructures responsible for the properties of these materials. At the same time, progress in synchrotron radiation techniques has ensured that these light sources remain a key tool of investigation, e.g. synchrotron radiation sources of the third generation are able to support magnetic imaging on a sub-micrometer scale. With the Sixth Mittelwihr School on Magnetism and Synchrotron Radiation the tradition of teaching the state-of-the-art on modern research developments continues and is expressed through the present set of extensive lectures provided in this volume. While primarily aimed at postgraduate students and newcomers to the field, this volume will also benefit researchers and lecturers actively working in the field.
Magnetism -- Synchrotron Radiation, Polarisation, Devices, New Sources -- Theoretical Basis of Photon Spectroscopies -- Free Electron Lasers -- Magnetic Imaging With Polarized Soft X-rays -- A Student`s Introduction to Resonant Inalestic Soft X-ray Scattering -- Synchrotron Radiation Studies of Topological Insulators -- Anisotropic X-ray Magnetic Linear Dichroism -- 25 Years of Magnetic Y-ray Dichroism -- Advanced Instrumentation of X-ray Magnetic Circular Dichroism -- Ultrafast Magnetization Dynamics Investigated With Femtosecond Time-Resolved X-ray Magnetic Circular Dichroism -- Index.
Keywords: Magnetism; Magnetic materials; Physical measurements; Measurement .; Nanoscale science; Nanoscience; Nanostructures; Spectroscopy; Microscopy; Superconductivity; Superconductors; Magnetism, Magnetic Materials; Measurement Science and Instrumentation; Nanoscale Science and Technology; Spectroscopy and Microscopy; Strongly Correlated Systems, Superconductivity